The Effect of Language Learning Strategies on Learners‟ Achievement and Attitude - Keezhatta, Muhammed Salim (International Journal of Psychosocial Rehabilitation, 2020)
This article goes for investigating the language learning strategies and their impact on the language learners which is considered to be influenced by learners’ individual differences as well as environmental factors. Every learner is unique and different from other peers on the basis of one or the other reason. So, to assess the phenomenon, the population of the study is chosen from department of Economics at the University of Lahore whom English is taught to hone their academic performance. The findings reveal that there are some fundamental and diverse factors which make the learners utilize the attitudes and practices among the target learners. The findings also suggest some practical implications for teachers and administrative authorities in the field of education.